Acoustic analyses of mortars prepared with recycled aggregates. (30th March 2023) - Bozkurt, Tarık Serhat
Graphical abstract: Highlights: The use of recycled aggregates in mortars was investigated for environmental sustainability. The improvement of sound absorption and sound insulation performance was researched. The analyses of compressive-flexural strength, open porosity, coefficient of water absorption, and luminance factor of mixtures were performed. The influences of the binder ratio and aggregate properties on the test results were examined. The influences of the basalt and glass fiber additives were investigated. Abstract: The use of aggregate types obtained from glass wastes and construction wastes was investigated in mortar mixtures. The sound absorption coefficient, sound transmission loss, flexural strength, compressive strength, open porosity ratio, density, luminance factor, and the coefficient of water absorption tests were performed in this study. The mortar content modifications, which are listed as binder ratio, aggregate gradation type, aggregate type, and fiber ratio, were examined. The influences of the mortar content changes on the measurement results were investigated. It was intended to improve the acoustic performance in line with mixture content modification. It was observed that as the binder ratio increases, the sound insulation performance and compressive strength can increase remarkably, and the sound insulation performance can improve especially at high frequencies. However, when the binder ratio increases, the sound absorption performance, open porosity ratio, and coefficient of water absorption can decrease in general terms. It was observed that using a very small aggregate particle size range, or using a well-graded aggregate mixture type instead of a uniformly-graded aggregate mixture type can reduce sound absorption performance. It was determined that the sound insulation level can increase as the aggregate particle size decreases, and the use of a well-graded aggregate mixture type rather than a uniform-graded aggregate mixture type is a good method to enhance compressive and flexural strength. It was mentioned that the utilization of lightweight aggregate in the mortar content can improve the sound absorption performance and reduce the sound transmission loss, compressive strength, and flexural strength performances. It was defined that the utilization of basalt or glass fiber in the mortar content can enhance sound absorption performance at high frequencies, sound insulation performance, and coefficient of water absorption.